Alternative splicing in a presenilin 2 variant associated with Alzheimer disease. Issue 4 (10th March 2019) - Braggin, Jacquelyn E.; Bucks, Stephanie A.; Course, Meredith M.; Smith, Carole L.; Sopher, Bryce; Osnis, Leah; Shuey, Kiel D.; Domoto‐Reilly, Kimiko; Caso, Christina; Kinoshita, Chizuru; Scherpelz, Kathryn P.; Cross, Chloe; et al.
Abstract: Objective: Autosomal‐dominant familial Alzheimer disease (AD) is caused by by variants in presenilin 1 ( PSEN1 ), presenilin 2 ( PSEN2 ), and amyloid precursor protein ( APP ). Previously, we reported a rare PSEN2 frameshift variant in an early‐onset AD case (PSEN2 p.K115Efs*11). In this study, we characterize a second family with the same variant and analyze cellular transcripts from both patient fibroblasts and brain lysates. Methods: We combined genomic, neuropathological, clinical, and molecular techniques to characterize the PSEN2 K115Efs*11 variant in two families. Results: Neuropathological and clinical evaluation confirmed the AD diagnosis in two individuals carrying the PSEN2 K115Efs*11 variant. A truncated transcript from the variant allele is detectable in patient fibroblasts while levels of wild‐type PSEN2 transcript and protein are reduced compared to controls. Functional studies to assess biological consequences of the variant demonstrated that PSEN2 K115Efs*11 fibroblasts secrete less A β 1–40 compared to controls, indicating abnormal γ ‐secretase activity. Analysis of PSEN2 transcript levels in brain tissue revealed alternatively spliced PSEN2 products in patient brain as well as in sporadic AD and age‐matched control brain. Interpretation: These data suggest that PSEN2 K115Efs*11 is a likely pathogenic variant associated with AD. We uncovered novel PSEN2 alternative transcripts in addition to previously reported PSEN2 splice isoforms associated with sporadic AD. In the context of a frameshift, these alternative transcripts return to the canonical reading frame with potential to generate deleterious protein products. Our findings suggest novel potential mechanisms by which PSEN variants may influence AD pathogenesis, highlighting the complexity underlying genetic contribution to disease risk.